The Level of Local Autonomy in the City of Cirebon within the Framework of Fiscal Decentralization - Meliza Indriyani; Ipik Permana (Publik : (Jurnal Ilmu Administrasi), 2026)
This study aims to analyze the level of local financial autonomy in the City of Cirebon within the framework of fiscal decentralization and the implementation of regional autonomy during the 2021–2024 period, identify inhibiting and supporting factors, and formulate strategies to enhance local financial autonomy. The study employs a qualitative approach supported by quantitative data, including reports on the implementation of the Regional Budget (APBD), regional financial autonomy ratios, and regional planning documents. Data collection techniques include in-depth interviews with officials from the Regional Financial and Revenue Management Agency (BPKPD), document analysis, and literature review. The research results indicate that the level of financial autonomy in Cirebon City remains in the low to moderate category, as evidenced by the high dependence on transfer funds from the central and provincial governments. This condition indicates that the objective of fiscal decentralization to strengthen local fiscal capacity has not yet been fully achieved. Major constraints include suboptimal management of Local Original Revenue (PAD), limited economic base, and potential revenue leakage, while supporting factors include regulatory support, technical assistance, and efforts to intensify local taxation. Strategies to enhance autonomy are directed toward optimizing PAD, strengthening local regulations, increasing community participation, and utilizing performance targets in the strategic plans of local government agencies. This study underscores the importance of strengthening local fiscal capacity as a prerequisite for the success of regional autonomy.